Physical Education Teachers’ Perceptions of Esports Adoption by KEMENPORA - Restu Dwi Firmansyah; Tedi Supriyadi; Ayi Suherman (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This research aims to determine the perceptions of physical education teachers in Cimahi, West Java regarding the designation of esports as a sport by the Ministry of Youth and Sports. Esports is an electronic sport that relies on an internet connection by presenting competition either as a team or individually to win matches that prioritize strategy without physical clashes. The method in this research uses a qualitative case study approach involving 10 selected physical education teachers in the city of Cimahi, West Java, where quite a lot of schools present esports extracurriculars through interview observations and data analysis documentation loaded in the NVivo 12 software application. The results obtained from this application is that all participants agree to the KEMENPORA's policy of classifying esports as sports. Esports also has a lot of relevance to the values ​​that grow in the school environment, including: critical thinking, creativity and courage to make decisions. The conclusion of this research is that esports is currently developing in several big cities and there is a need for equitable distribution through outreach to the community, schools and parents of students. In this way, esports is no longer considered an unproductive activity but rather a sport that is being carried out without physical conflict, but must always be monitored and accommodated the potential of students by the school and the parents of the children concerned